2017
DOI: 10.1186/s12951-017-0278-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy analysis of anti-microbial peptides, LL-37 and indolicidin upon conjugation with CNT, in human monocytes

Abstract: BackgroundAntimicrobial peptides (AMPs) have the potential to serve as an alternative to antibiotic. AMPs usually exert bactericidal activity via direct killing of microbial pathogens. Reports have proposed that by harnessing innate immune activation, AMPs can regulate pathogen invasion and may control infection. It has been reported that AMPs could be utilized to activate the innate mucosal immune response in order to eliminate pathogenic infections. This way of controlling pathogen infection, by activating h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…122 Recently, Pradhan and colleagues (2017) conjugated LL-37 and indolicidin to short multi-walled carbon nanotubes (SMCNTs); the in vitro immunoregulatory activity of nano-conjugates was significantly higher than that of the dissociated forms of indolicidin and LL-37, and peptide activity was maintained even at a concentration that is 1000 times lower (0.02 μg mL −1 of nano-conjugates and 20 μg mL −1 of free peptides). 75…”
Section: Amp Nanoparticle Systemmentioning
confidence: 99%
“…122 Recently, Pradhan and colleagues (2017) conjugated LL-37 and indolicidin to short multi-walled carbon nanotubes (SMCNTs); the in vitro immunoregulatory activity of nano-conjugates was significantly higher than that of the dissociated forms of indolicidin and LL-37, and peptide activity was maintained even at a concentration that is 1000 times lower (0.02 μg mL −1 of nano-conjugates and 20 μg mL −1 of free peptides). 75…”
Section: Amp Nanoparticle Systemmentioning
confidence: 99%
“…Some of these AMPs, such as alamethicin, porcine protegrin-1, indolicidin, temporin-She, and AP-64, are considered cytotoxic for human use, while the rest of the AMPs (magainin 2, HBD2, LL-37, nisin, Pro10-1D, and protein-glutamine gamma-glutamyltransferase 2) are considered less toxic and safe to use. Among all these safe-to-use AMPs, nisin is used extensively in clinical trials [ 25 , 26 ]. More in vitro and in vivo clinical trials are required to further explore its safety.…”
Section: Recently Tested Peptidesmentioning
confidence: 99%
“…It has been documented that the surface of CNTs can decorate various functional groups and provides binding sites, thus, improving the dispersibility and biocompatibility of uploaded drugs ( Zhang et al, 2012 ). Pradhan et al (2017) reported that SM-CNTs conjugated to LL-37 (LLGDFFRKSKEKIGKEFKRIVQRIKDFLRNLVPRTES) or indolicidin by the use of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide (EDC-NHS) conjugation protocol to impair side effects. The results demonstrated that the two-peptide conjugation with CNT was 1,000-fold lower than the dosage of free AMPs required for intracellular biological functions, suggesting that SM-CNTs improved the immune-modulatory efficacy of LL-37 and indolicidin, while efficiently reducing the dosage of peptide agents.…”
Section: Inorganic Materials Nanosystems Containing Antimicrobial Peptidesmentioning
confidence: 99%